Isolation and characterization of new microsatellite markers for application in population genetic studies of Caiman latirostris and related species - Amavet, Patricia Susana; Rueda, Eva Carolina; Siroski, Pablo Ariel; Larriera, Alejandro; Saidman, Beatriz Ofelia (Amphibia-reptilia, 2015)
Wild populations of Caiman latirostris are subject to sustainable use programs in Argentina, becoming a species with important impact in the regional economy, based in their skin and meat. Genetic studies are fundamental to acquire information on important parameters for conservation and management, which may be obtained from analysis of molecular markers. Some microsatellites have been previously isolated in this species, but due to some difficulties in using them, we obtained new ones using Next Generation Sequencing approach. This study reports eight new microsatellites for C. latirostris and tests their utility in a related species, Caiman yacare, with successful application in population genetics and mating systems studies. In addition, we shared data about a novel and fast bioinformatics tool to find microsatellites and to design their corresponding primers.